# If #f(x) =-e^(-3x-7) # and #g(x) = -2sec^2x #, what is #f'(g(x)) #?

By signing up, you agree to our Terms of Service and Privacy Policy

To find ( f'(g(x)) ), first, we need to find the derivative of ( f(x) ) with respect to ( x ), then substitute ( g(x) ) into the derivative of ( f(x) ).

Given ( f(x) = -e^{-3x-7} ), we find ( f'(x) = 3e^{-3x-7} ).

Now, substituting ( g(x) ) into ( f'(x) ), we have:

[ f'(g(x)) = 3e^{-3(g(x))-7} ]

Substitute ( g(x) = -2\sec^2(x) ) into the expression:

[ f'(g(x)) = 3e^{-3(-2\sec^2(x))-7} ]

Therefore, ( f'(g(x)) = 3e^{6\sec^2(x)-7} ).

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7